Assessment of lignin residues from bioethanol production of olive stones as green chemical thickener of epoxidized linseed oil - Cortés-Triviño, Esperanza; Valencia, Concepción; Franco, Jose María; Oliva, Jose Miguel; Manzanares, Paloma; Eugenio, M.Eugenia; Ibarra, David (Springer Nature, 2024)
This work focused on the characterization of lignin residues from bioethanol production of olive stones (OS) and the use of these residues to chemically thicken epoxidized linseed oil (ELO). OS were processed by an acid/steam explosion pretreatment, followed by pre-saccharification, using different enzymedosages, and simultaneous saccharification and fermentation. The chemical composition of the OS lignin residues was analysed, revealing a high lignin content (66.6–69.5%), and lower quantities of glucan (17.4–19.3%) and xylan (2.8–2.9%). Whereas, the structural properties of OS lignin residues were characterized by Fourier-transform infrared (FTIR) spectroscopy, nuclear magnetic resonance (NMR), thermogravimetric analysis (TGA) and size exclusion chromatography (SEC). OS lignin residues displayed the main inter-unit linkages (-´ resinol (51.0–59.0%), followed by -O-4´ alkyl aryl ethers (27.0–35.2%) and -5´ phenylcoumaran (11.4–13.2%) substructures), high molecular weights (22000-25900 Da), low S/G ratios (1.2-1.5) and phenolic compounds (48–55 mg GAE/g lignin). Moreover, OS lignin residues were dispersed in ELO to obtain thickened formulations, which were characterized by FTIR and NMR. Oil thickening was achieved by promoting the chemical crosslinking between lignocellulose hydroxyl groups and ELO epoxy groups, enabling the compatibilization of both components. Up to 10-fold viscosity increment of the resulting thickened formulations in relation to ELO’s viscosity was observed. Besides, thickened formulations exhibited viscoelastic properties, evincing oil structuration to some extent.
Keywords: epoxidized vegetable oil; green thickener; intrinsic viscosity; lignin characterization; lignin residues; olive stones